Essay Writing Through Quantum Learning With Mind Mapping Strategy - Arini, Ni Wayan; Tristiantari, Ni Ketut Desia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
This research was aimed atfinding out the improvement in essay writing skill in Scientific Writing course among the students of Elementary School Teacher Department of class G in semester VI in the academic year 2015/2016 after implementing Qauntum Learning with Mind Mapping Strategy. This study used classroom action research design that was done gradually in multicyles. Each cycle consisted of planning, action, observation/evaluation and reflection. This study was done at Jurusan PGSD, FIP (Elementary School Teacher Department, Faculty of Education), Undiksha in the odd semester in the acacemic year 2015/2016 from April to November. The subjects were the students of class G in semester VI at Elementary School Teacher Department, Faculty of Education with the total number of 43 students. The data on the students’ essay writing skill were obtained by using essay writing skill test. The result showed that (1) the mean score of the students’ essay writing skill in cycle I was 73.4, in cycle II it reached 81.5, (2) the number of students who belonged to “good” and “very good” categories in cycle I was only 58.5, in cycle II it reached 88.4%, and (3) based on the computationi of gain score it was found that the improvement in the students’ writing skill was 0.333, falling into “average” category. It can be concluded that the implementation of Quantum Learning with Mind Mapping Strategy could improve essay writing skill of the sudents in class G in semester VI in Elementary School Teacher Education Undiksha in the academic year 2015/2016.